(untitled) (Global Journal of Computer Science and Technology, 2012)
One of the fundamental function of an operating system is scheduling. There are 2 types of uni-processor operating system in general. Those are uni-programming and multi-programming. Uni-programming operating system execute only single job at a time while multiprogramming operating system is capable of executing multiple jobs concurrently. Resource utilization is the basic aim of multiprogramming operating system. There are many scheduling algorithms available for multi-programming operating system. But our work focuses on design and development aspect of new and novel scheduling algorithm for multi-programming operating system in the view of optimization. We developed a tool which gives output in the form of experimental results with respect to some standard and new scheduling algorithms e.g. First come first serve, shortest job first, round robin, optimal and a novel cpu scheduling algorithm etc.